Karakteristik Awal Pembuatan Glukosa dari Ampas Kayu dengan Microwave - I Nyoman Sudiana; D.K. Sutiari; P. Endang S (Universitas Halu Oleo, 2016)
A study of on the degradation of cellulosic sawdust to glucose by applied a commercial microwave oven for treatment has been successfully performance . The effects of the microwave compared to those of the conventional method were found. The reagents used in this experiment is an hydrochloric acid (HCl). Experimental results showed that the microwave-assisted pretreatment on the lignocellulosic sawdust resulted in a higher glucose compared to the conventional method. The treatment was also performed in lower temperatures and lower reagent concentrations.